Endoscopic tissue sampling - Part 1: Upper gastrointestinal and hepatopancreatobiliary tracts. European Society of Gastrointestinal Endoscopy (ESGE) Guideline - Pouw, Roos E.; Barret, Maximilien; Biermann, Katharina; Bisschops, Raf; Czako, Laszlo; Gecse, Krisztina B.; De Hertogh, Gert; Hucl, Tomas; Iacucci, Marietta; Jansen, Marnix; Rutter, Matthew; Savarino, Edoardo; et al. (Endoscopy, 2021)
Main Recommendations
CRIS-Team WoS Importer:2021-10-01